Introduction to public finance and taxation - Mapesa Haruni Jeremia; Kiria Joseph Simon (Mzumbe University, 2026)
This book introduces foundation topics on public finance and a broad range of topics in taxation theory and tax laws in Tanzania. The book intends to fill a gap that exists as a result of several developments in public revenue and expenditure policy reforms and changes in fiscal policy and tax laws in Tanzania. New tax laws have been enacted such as the Tax Administration Act 2015, and existing laws have been repealed (e.g. Value Added Tax 1997) and replaced with new tax laws (e.g. the Value Added Tax Act of 2014). Similarly, there have been several legislative developments in the existing tax laws which amend existing tax laws. All these reforms necessitate for amendment of existing tax textbooks and/or development of new taxation textbooks that would provide comprehensive material on the interpretation and application of the new tax laws and the amended tax laws. This book fills this gap and the book comes at a time when lecturers, university students, professionals, and practitioners are in urgent need of such books. Most of the books written before these changes are outdated and cannot provide adequate guidance on the interpretation and application of the new and amended tax laws and current trends in public finance administration